Aplikasi Laporan Keuangan Menggunakan Database Terdistribusi Azzam Komputer (Information Technology and Telematics, 2015)
Abstrak— The financial statements are important for any company or entity, including azzam computer. The process is easy and the accuracy of the report valid data and structured into a vital part of the financial statements.In order to facilitate the process of reporting required to support the application as needed processing and presentation of data.Structured data that can facilitate the processes undertaken.Making financial statements azzam computer is still manual so that employees need to work twice to make a report and check the data structure.  To  create  structured  data  we  need  a database to store data based on a specific sequence. Accuracy of data in the database can be updated to be valid and correctly either in real time or in a certain time lag. In this case the distributed database has a major role in the distribution of data is valid and can be  updated  in  real  time  or  in  a  certain  time  lag. This research aims to design applications that use the financial statements distributed database with multi- master replication to distribute its database. This research is expected to facilitate the employee in making  the  report,  but  the  accuracy  of  the  data remains valid and structured in its presentation.   Keywords: laporan keuangan, database,database terdistribusi